Strategi dan Tantangan Pemerintah Kolonial Belanda dalam Penanganan Kolera di Cirebon Abad 19 - Marom, Ahmad Taufal; Syafaah, Aah (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
Outbreaks of cholera caused by the Vibrio cholerae bacteria are characterized by rapid transmission and pandemic potential, or alternatively, by slower progression, resulting in patients becoming dehydrated due to the excessive production of diarrhoeic stools. At the outset of its emergence, cholera was perceived as a prevalent ailment, given that the symptoms were commonly observed within the community, including vomiting and diarrhea. However, this perception only emerged following the deaths of numerous individuals presenting with these same symptoms. Since 1821, newspapers have reported that cholera is not an ordinary disease, given the high mortality rate and its rapid spread, particularly in Java. Historically, this disease had occurred, but it was readily surmountable due to the colonial government’s acceptance of the palace officials’ recommendation to seek Kyai Muqoyyim Buntet’s assistance in addressing the cholera outbreak. By forging a collaborative relationship with the local population, the Dutch colonial government was able to combat the cholera epidemic successfully. This involved combining modern healthcare techniques with traditional healing practices that had been trusted by the community for generations